Guidobaldo del Monte (1545-1607) Theory and Practice of the Mathematical Disciplines from Urbino to Europe - Antonio Becchi (ed.) (Proceedings 4: Max Planck Research Library for the History and Development of Knowledge, 2013)
Guidobaldo Marquis dal Monte has long been identified as a key figure in the history of the mathematical disciplines in the Renaissance. The contributions brought together in this volume examine all the key aspects of the Marquis dal Monte's activities, ranging from mechanics and the science of perspective to architecture and geometry. Some of the essays provide intellectual analyses of Guidobaldo's works, including their significance and reception, others document his activities in the design of mathematical instruments, in civil and military architecture, and in his professional travels and contacts with Galileo. Many of the contributions rely on archival research shedding new light on his activities. As a result, Guidobaldo appears in a new light and as a key figure not only in the Duchy of Urbino, but also on an Italian and European stage.